2015
DOI: 10.4028/www.scientific.net/amr.1130.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu(II) on Bio-Scorodite Crystallization Using <i>Acidianus brierleyi</i>

Abstract: The effect of different concentrations of Cu (II) on microbial scorodite (FeAsO4⋅2H2O) formation was investigated by using thermo-acidophilic iron-oxidizing archaeon, Acidianus brierleyi. In the presence of 8-16 mM Cu (II) microbial Fe (II) oxidation and cell growth was only marginal. Its As (III) oxidation ability was especially severely inhibited by the presence of Cu (II), consequently disabling scorodite formation. However, when scorodite seed crystals were fed, Ac. brierleyi readily oxidized Fe (II) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Formation of bioscorodite has been reported in thermo-acidophilic Fe(II)-oxidizing archaeon Ac. brierleyi under specific cultivation conditions as well, with an optimal pH of 1.5 to 2.0 and temperature of 70 °C [ 82 , 83 ]. It was shown that bioscorodite can still be crystallized in the presence of Cu(II) by feeding scorodite seeds from synthetic copper-refining As(III)-bearing wastewaters [ 83 ].…”
Section: Bioscoroditementioning
confidence: 99%
“…Formation of bioscorodite has been reported in thermo-acidophilic Fe(II)-oxidizing archaeon Ac. brierleyi under specific cultivation conditions as well, with an optimal pH of 1.5 to 2.0 and temperature of 70 °C [ 82 , 83 ]. It was shown that bioscorodite can still be crystallized in the presence of Cu(II) by feeding scorodite seeds from synthetic copper-refining As(III)-bearing wastewaters [ 83 ].…”
Section: Bioscoroditementioning
confidence: 99%